The Effect of 3rd Carpometacarpal Arthrodesis in the Outcomes of Total Wrist Fusion Using Modern Plate Technology - Rioux-Forker, Dana; Patel, Raahil S.; Hinchcliff, Katharine M.; Shin, Alexander Y. (Journal of Wrist Surgery, 2023)
Background The inclusion of the third carpometacarpal (CMC) joint in the fusion mass in total wrist fusion (TWF) remains controversial. Our goal was to evaluate the clinical outcomes and effects of third CMC joint arthrodesis compared with bridging the CMC joint during TWF. A retrospective chart review was performed. Outcomes assessed included hardware loosening, hardware failure, symptomatic hardware necessitating removal, and need for revision arthrodesis.Case Description/Literature Review We found that concomitant third CMC joint arthrodesis was associated with a significantly reduced rate of radiocarpal and midcarpal joint nonunion, hardware loosening, and symptomatic hardware removal when compared to bridging of the CMC joint. There was no significant difference in hardware failure rates or the need for revision arthrodesis.Clinical Relevance When using a contoured dorsal spanning plate, concomitant CMC joint arthrodesis should be considered during TWF to mitigate against hardware loosening and symptomatic hardware.Level of Evidence Level IV
Keywords: carpal arthrodesis; carpometacarpal arthrodesis; total wrist arthrodesis; fusion